2016
DOI: 10.1002/cncr.30200
|View full text |Cite
|
Sign up to set email alerts
|

Risk and impact of pulmonary complications in survivors of childhood cancer: A report from the Childhood Cancer Survivor Study

Abstract: Background Pulmonary complications after cancer therapy are varied. We describe pulmonary outcomes among childhood cancer survivors and evaluate their impact on daily activities. Methods The incidence of pulmonary outcomes (asthma, chronic cough, emphysema, lung fibrosis, oxygen need, recurrent pneumonia) reported among 5-year cancer survivors (n=14,316) and death from pulmonary causes among all eligible survivors (n=20,690) in the Childhood Cancer Survivor Study (CCSS) were compared to sibling controls (n=4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 29 publications
4
65
1
3
Order By: Relevance
“…We found chronic respiratory symptoms to be more common among children exposed to second hand smoke at home although the exposure group was small. Studies of adult survivors of childhood cancer reveal lower smoking rates than in the general population 4, 34, 35 and minor differences in smoking prevalence based on exposure to cardiopulmonary toxic therapies; this suggests differences in behavior based on perceived risk. 34 Further studies are needed to determine if knowledge of subclinical decreases in PFT parameters prevent smoking initiation among adolescent or young adult survivors of high-risk NB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found chronic respiratory symptoms to be more common among children exposed to second hand smoke at home although the exposure group was small. Studies of adult survivors of childhood cancer reveal lower smoking rates than in the general population 4, 34, 35 and minor differences in smoking prevalence based on exposure to cardiopulmonary toxic therapies; this suggests differences in behavior based on perceived risk. 34 Further studies are needed to determine if knowledge of subclinical decreases in PFT parameters prevent smoking initiation among adolescent or young adult survivors of high-risk NB.…”
Section: Discussionmentioning
confidence: 98%
“…1, 2 Data from the Childhood Cancer Survivor Study demonstrate that survivors have an increased risk of lung fibrosis, recurrent pneumonia, chronic cough, pleurisy, requirement for supplemental oxygen, and exercise-induced shortness of breath more than five years post-diagnosis. 3, 4 Increased mortality due to pulmonary causes among cancer survivors has also been reported. 5 Limited information is available on pulmonary outcomes in survivors of high-risk neuroblastoma (NB).…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory morbidity ranges in severity from subclinical to severe and life threatening complications which may impact on quality of life . Available intelligence to date on respiratory morbidity is predominantly obtained by self‐report and/or utilises sibling control data.…”
Section: Introductionmentioning
confidence: 99%
“…Available intelligence to date on respiratory morbidity is predominantly obtained by self‐report and/or utilises sibling control data. Studies have shown that CCS have an increased risk of various respiratory conditions including lung fibrosis, pneumonia, chronic cough, pleurisy, use of supplemental oxygen, abnormal chest wall and exercise‐induced shortness of breath, compared to sibling controls . Limitations of using sibling controls are that both the CCS and the sibling control are likely to share the same environmental and genetic risk factors, therefore the true excess risk of respiratory disease in CCS may be under‐estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer in children is rare; only about 1% of new cancer cases [1] in the United States occur among children younger than 19 years of age [2]. Although advances in treatment have increased the overall 5-year survival rate for childhood cancers to approximately 80%, cancer is still the second leading cause of death (following accidents) in children aged 5 to 14 years with slightly increased rates in males and white children [3].…”
Section: Introductionmentioning
confidence: 99%